Clinical focus. Boston University Doctor of Science degree program: clinical doctorate in audiology. - Kidd GD Jr.; Cox LC; Matthies ML (American Journal of Audiology, 2003)
This article describes the development of the Boston University Clinical Doctoral Program in Audiology dating from its inception in 1985 to the present. The issues surrounding the establishment of the clinical doctorate, entering the program, and the curriculum are discussed. The unique features of this program and associated resources available within the clinical and scientific community of the greater Boston area are highlighted.